PENGARUH KOMPENSASI DAN KEMAMPUAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT PRATAMA ABADI INDUSTRY JX - Siti Rohayati (Jurnal Pijar, 2022)
This study aims to determine how the effect of compensation and work ability on employee performance at PT Pratama Abadi Indusy JX. The number of samples used in this study were 77 respondents who were determined using the Slovin formula. The data analysis method used is validity test, reliability test and multiple linear regression. The results of the study indicate that either partially or simultaneously compensation and work ability have a significant effect on employee performance at PT. Pratama Abadi Industry JX